Let's Vote! - Illinois State Board of Education, Springfield; Illinois State Board of Education, Springfield; Illinois State Board of Elections, Springfield ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
These activities are intended to acquaint elementary students with the voting process. Students in grades K-4 are introduced to vocabulary concerning voting through games and classroom discussions. A voting area is simulated in the classroom. Students are given the opportunity to vote for their favorite dog, bird, and wild animal. So that they can compare candidates within each category, students are given charts describing characteristics of various dogs, birds, and wild animals. Pre-election day activities include discussions of the candidates, making clay figures of the candidates, and having each child tell why he or she thinks his or her favorite is the best. Students are made acquainted with the concept of voter qualification through classroom discussions. Students are also introduced to voting procedures, e.g., students make signs to be used in and around the polling place, and they make badges for the election judges to wear on election day. Many student handouts concerning voting that can be used in the activities are included in the publication, e.g., a connect-the-dots picture of a boy voting, a find-the-way to the polling place maze, crossword puzzles, and pictures of the candidates to color. (RM)
Educational level discussed: Elementary Education.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Basic Vocabulary; Citizen Participation; Citizenship Education; Citizenship Responsibility; Elections; Elementary Education; Learning Activities; Social Studies; Voting; Guides, Classroom -- Teacher